Rethinking PES in community forestry: Understanding incentives in socio-ecological context - Lawry, Steven (2023)
Steven Lawry CGIAR SEMINAR SERIES Payments for Ecosystem Services: Win-Win Solutions? Co-organized by IFPRI, the CGIAR, and Germany’s Federal Ministry for Economic Cooperation and Development (BMZ) Session at Tropentag 2023 SEP 21, 2023 - 7:45 TO 9:15AM EDT